2006
DOI: 10.1097/01.mph.0000243666.79303.45
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Medication Adherence in Pediatric Acute Lymphoblastic Leukemia: A Review

Abstract: Significant numbers of children and adolescents with acute lymphoblastic leukemia (ALL) do not adequately adhere to their treatment regimen. Failure to take the appropriate amount of prescribed medication may result in disease relapse. Although a number of research studies have sought to identify the factors associated with medication nonadherence in this group, no systematic study has sought to evaluate the efficacy of intervention packages in improving adherence. The aim of the current paper is to provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 48 publications
2
47
0
4
Order By: Relevance
“…The rate of nonadherence could not be precisely studied here with the small sample size necessary for the mixed methodology chosen, which combined in-depth interviews and self-administered questionnaires. It is also difficult to compare this nonadherence rate with previous studies that used different definitions of adherence [18]. However, these results confirm that adherence toward leukemia maintenance therapy is sometimes inadequate, as has been described in several studies [4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The rate of nonadherence could not be precisely studied here with the small sample size necessary for the mixed methodology chosen, which combined in-depth interviews and self-administered questionnaires. It is also difficult to compare this nonadherence rate with previous studies that used different definitions of adherence [18]. However, these results confirm that adherence toward leukemia maintenance therapy is sometimes inadequate, as has been described in several studies [4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 50%
“…There is no operational definition of leukemia maintenance therapy adherence [18], although the risk of relapse depends on the maintenance treatment quality [14][15][16]. The physician evaluation finally may be more pragmatic and efficient, as we cannot be sure when forgetfulness is sufficient to impair the chances of recovery.…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…39 Second, poor patient compliance to the prescribed oral doses of 6MP/MTX has been indicated as a risk factor for relapse. [40][41][42] Social, psychological and medical disorders may influence to which extent adolescents take their prescribed therapy, 43 and the problem is not trivial. Both electronic monitoring 40 and drug metabolite measurements 44 have indicated that 10-20% of childhood ALL patients intermittently fail to take their oral medication, with a few percent being consistently non-compliant, a problem that seems more frequent among adolescents.…”
Section: Discussionmentioning
confidence: 99%